Diagnosis of teaching-learning Physics difficulties in Elementary and High School and implications of skills and abilities of the new guidelines (Research, Society and Development, 2021)
This work presents the results of a research that aimed to analyze the causes of the gap in physics teaching in the final years of elementary school, resulting in difficulties in learning physics in high school and the implications of the new guidelines for elementary and high school education. . The research included the review of works that seek to characterize the causes of difficulties presented by students in the early years of high school. In addition, information was sought about topics that should be addressed in the last years of elementary school and in the first year of high school, according to the BNCC and the PCNs, which indicate the skills and competencies that need to be developed. Thus, questionnaires referring to the skills and competencies that should be developed in the final years of elementary school, a questionnaire aimed at students, and another on the main difficulties in the classroom aimed at teachers were created. Through these questionnaires, the answers of 50 science teaching teachers from the final years of elementary school and 100 students from the first year of high school were analyzed, taking into account the topics of the documents of the PCN and BNCC. The results indicate difficulties in teaching physics both for teachers, who often fail to present some topics due to their training and for students who as a result have difficulties embarking on the first year of high school, indicating the need for teacher training to better serve the training of students.